2004
DOI: 10.1124/mol.104.008847
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Differences between Human and Guinea Pig Histamine H1 Receptors: Asn84 (2.61) as Key Residue within an Additional Binding Pocket in the H1 Receptor

Abstract: We tested several histamine H 1 receptor (H 1 R) agonists and antagonists for their differences in binding affinities between human and guinea pig H 1 Rs transiently expressed in African green monkey kidney (COS-7) cells. Especially, the bivalent agonist histaprodifen-histamine dimer (HP-HA) shows a higher affinity for guinea pig than for human H 1 Rs. Based on the structure of HP-HA, we have further identified VUF 4669 [7-(3-(4-(hydroxydiphenylmethyl)piperidin-1-yl)propoxy)-4-oxochroman-2-carboxylic acid] as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
(58 reference statements)
1
47
0
1
Order By: Relevance
“…Human and guinea pig H1R models based on the bovine rhodopsin structure were also published [16]. Several known agonists and antagonists were docked and complexes were further refined by MD simulations.…”
Section: H1 Receptormentioning
confidence: 99%
“…Human and guinea pig H1R models based on the bovine rhodopsin structure were also published [16]. Several known agonists and antagonists were docked and complexes were further refined by MD simulations.…”
Section: H1 Receptormentioning
confidence: 99%
“…Unfortunately, bulky H 1 R agonists exhibit considerably lower potency and efficacy at the hH 1 R than at the guinea pig H 1 R (gpH 1 R), limiting their usefulness as tools for studying the hH 1 R (Seifert et al, 2003). The molecular basis for the differences in pharmacological properties between hH 1 R and gpH 1 R has recently been elucidated (Bruysters et al, 2005). A further complication is that, at concentrations in the range of 10 M to 1 mM, 2-phenylhistamines may activate G-proteins directly, i.e., in a receptor-independent manner (Seifert et al, 1994;HagelĆ¼ ken et al, 1995;Klinker et al, 1996).…”
mentioning
confidence: 99%
“…Several mutational studies identified amino acids interacting with antagonists in the H 1 R binding pocket (Wieland et al, 1999) and amino acids responsible for species differences between hH 1 R and gpH 1 R (Bruysters et al, 2005;Strasser et al, 2008b) concerning agonists. Because there has been no thermodynamic study of ligand binding to the H 1 R, the aim of this study was to analyze the following questions: 1) Is there a thermodynamic discrimination between agonists and antagonists at hH 1 R and gpH 1 R?…”
mentioning
confidence: 99%